DESIGN FACTORS OF WELDING COLUMNS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the main methods and approaches used in the design of welded columns. It describes the processes of determining the load capacity, stability, and mechanical properties of welded columns through structural calculations, computer modeling, and experimental studies. Based on the results, key factors for selecting materials and technologies to enhance the efficiency of welded columns are highlighted. New technologies and materials have ensured the reliability and long-term performance of welded columns. The article also addresses the main design challenges and future research directions.